Empirical study: Influence of trade value offered by e- marketers on intention quotient of Mumbai based online shoppers to shop online - Shaikh, Dr. Asmat Ara; Shaikh, Dr. Mohammed Zafar; Kumar, Mr. Anuj (The journal of contemporary issues in business and government, 2021)
Online shopping provides many benefits to online shoppers, which includes ease, numerous collections, reasonable price, innovative services, personal attention, and quick access to information. A detailed study depicting Trade factors variables and their association/relationship with Mumbai-based online shoppers Intention Quotient has been done in this paper so that an understanding of the underlying factors develops as a premise for future studies. What defines Intention Quotient? Does the Trade factor act as a factor to influence the Intention Quotient of Mumbai-based online shoppers to shop online? How much online shoppers concerned about the value of money to shop online? Does negotiable cost affect online shoppers Intention Quotient? What is the effect of reasonable price on Intention Quotient? Does offers, and discount has an impact on online shoppers purchase behavior? Do multiple payment options influence the Intention Quotient of Mumbai base online shoppers?